Rule Based Approach for sarcasm Detection on Twitter Data - Priyanka Rani, Poonam katyal (International Journal of Advanced Science and Technology, 2020)
In today’s Era, online Social network portray an important role in analyzing the market of a product, a movie and even people’s inclination towards a political party and for this analysis sarcasm is a major hurdle which is a witty way of expression now a days, where message has a hidden meaning which could be a way to criticize or making fun by playing through words, which is a major challenge to extract.